Understanding multi-homing and switching by platform drivers - GUO, Xiaotong (Institutional Knowledge at Singapore Management University, 2023)
Freelance drivers in the shared mobility market frequently switch or work for multiple platforms, affecting driver labor supply. Due to the importance of driver labor supply for the shared mobility market, understanding drivers’ switching and multi-homing behavior is vital to managing service quality on – and effective regulation of – mobility platforms. However, a lack of individual-level data on driver behavior has thus far impeded a deeper understanding. This paper taxonomizes and estimates perceived switching and multi-homing frictions on mobility platforms. Based on a structural model of driver labor supply, we estimate switching and multi-homing costs in a platform duopoly using public and limited high-level survey data. Estimated costs are sizeable, and reductions in multi-homing and switching costs significantly affect platform market shares and driver welfare. Driver labor supply elasticity with respect to platform wage is also discussed considering both multi-homing and switching frictions.